Patterns in inversion sequences I - Corteel, Sylvie; Ma; Savage, Carla D; Weselcouch, Michael (Discrete Mathematics and Theoretical Computer Science, 2016)
Permutations that avoid given patterns have been studied in great depth for their connections to other fields of mathematics, computer science, and biology. From a combinatorial perspective, permutation patterns have served as a unifying interpretation that relates a vast array of combinatorial structures. In this paper, we introduce the notion of patterns in inversion sequences. A sequence (e1,e2,…,en)(e1,e2,…,en) is an inversion sequence if 0≤ei<i0≤ei<i for all i∈[n]i∈[n]. Inversion sequences of length nn are in bijection with permutations of length nn; an inversion sequence can be obtained from any permutation π=π1π2…πnπ=π1π2…πn by setting ei=|{j | j<i and πj>πi}|ei=|{j | j<i and πj>πi}|. This correspondence makes it a natural extension to study patterns in inversion sequences much in the same way that patterns have been studied in permutations. This paper, the first of two on patterns in inversion sequences, focuses on the enumeration of inversion sequences that avoid words of length three. Our results connect patterns in inversion sequences to a number of well-known numerical sequences including Fibonacci numbers, Bell numbers, Schr\"oder numbers, and Euler up/down numbers.